Training of Canva-Based Learning Media Usage - Idarianty, Idarianty; Yusraini, Yusraini; fahri, Ismail; Ramadhano, Yanri; Afifah, Yuliana; Fikri, Ahmad; Hasirah, Hasirah (Lembaga Dongan Dosen, 2025)
Canva is a text-centric graphic design program frequently utilized for presentation materials. The implementation of the Canva application can assist and educate students in facilitating the creation of effective presentation materials. This community service initiative was conducted at the Al-Mujaddin Islamic Institute in Sabak, West Tanjung Jabung, Jambi, Indonesia, which has not fully utilized Canva. This community service initiative aims to train lecturers and students in enhancing their skills in developing effective presentation materials via Canva. This activity commences with the presentation of materials to the service participants, followed by training on how to produce presentation materials using Canva. Through presentation training and the use of the Canva application, lecturers and students are anticipated to effectively use these skills in the learning process of subjects necessitating technology-mediated presentations and to utilize presentation training appropriately. Prior to the training, many participants were unaware of the diverse features and advantages of the Canva application. Following the training, participants expressed satisfaction with their experience using Canva and acquired new knowledge and skills applicable to students. The utilization of the Canva application by participants is highly advantageous, enhancing interest, engagement, and self-assurance, which subsequently fosters creativity and comprehension of the subject matter. Recommendations entail offering professional development opportunities for professors and students, as well as delivering feedback to enhance the utilization of Canva in the classroom. This seminar highlights the potential of technology, namely the integration of Canva in educational settings, to improve motivation, creativity, and teamwork.